(untitled) (Scientific journal of the Fergana State University, 2026)
Abstract This scientific research provides a detailed analysis of the socio-pedagogical foundations and modern approaches to shaping national identity through sports. The focus is on the formation of national identity through sports, specifically examining the role of sports in strengthening nationalism, values, and national traditions. The study discusses the significance of national sports, the role of sports in social development, and its impact on the youth’s sense of national identity. Through modern approaches, the research examines the mechanisms for supporting national identity in the context of digital technologies, social media, and globalization. The findings include proposals for developing national identity mechanisms through sports, improving social and pedagogical programs, and ensuring effective cooperation between government, education, and society. The goal of this work is to provide greater clarity on these issues and identify ways to enhance the effectiveness of shaping national identity through sports.